Incentivized self-vaccination for global measles eradication - Benjamin L. Sievers; Robert E. Sievers; Eric L. Sievers (Elsevier, 2022)
Measles-we've become inured to its cruel, insidious impact as it kills over 100,000 children yearly because of suboptimal vaccination coverage. It does not have to be this way. A familiar, safe, exceptionally effective measles vaccine saves lives and permanent, global measles eradication is within reach. But now we need to be clever and courageously explore new strategies to save lives. Firstly, let us enable people to vaccinate themselves, not with a needle and syringe, but with a quick inhaled puff of dry powder vaccine. Secondly, let us provide micro-payments using digital currency to incentivize those who vaccinate themselves. Thirdly, let us leverage learnings from how our social networks guide our behaviors to further encourage self-vaccination. Fourthly, let us inspire friendly regional competition among communities vying for the highest proportion of citizens who show measles neutralizing antibodies in spot saliva samples. With global cooperation and relentless determination, we eradicated smallpox. Next up? Measles.